CONFERENCE REPORT – THE THIRD SOUTHERN AFRICAN PSYCHOLOGY STUDENTS’ CONFERENCE, JUNE 2013 - Kiguwa, Peace (PINS-Psychology in Society, 2025)
The third biannual Southern African Psychology Students’ Conference (24-28 June 2013) was the largest yet since its inception in 2009 Gaborone, Botswana. Boasting a total of 163 presentations the conference was jointly hosted by the Psychology departments of the University of South Africa and the University of the Witwatersrand.